2021
DOI: 10.3389/fcell.2021.555248
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the ex vivo Effects of Tamoxifen on Adipose-Derived Stem Cells: A Pilot Study

Abstract: Autologous fat grafting (AFG) is a safe and minimally invasive procedure to correct soft tissue defects. The benefit of AFG is attributed to adipose-derived stem cells (ASCs) in fat tissue graft. This technique is useful also in patients undergoing reconstructive surgery following quadrantectomy for breast cancer. However, these patients are frequently treated with tamoxifen. We evaluated the ex vivo effects of tamoxifen on ASCs to understand if cellular functions of ASCs are affected. We selected 24 female pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
0
3
3
Order By: Relevance
“…On the other hand, further studies showed controversial results. In contrast to the present results, it was postulated that tamoxifen does not affect cellular proliferation, vascular endothelial growth factor secretion and apoptosis of ASC [ 42 ]. Furthermore, the gene expression assessment demonstrated no impairment in the differentiation capacity of ASC after tamoxifen treatment [ 42 ].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…On the other hand, further studies showed controversial results. In contrast to the present results, it was postulated that tamoxifen does not affect cellular proliferation, vascular endothelial growth factor secretion and apoptosis of ASC [ 42 ]. Furthermore, the gene expression assessment demonstrated no impairment in the differentiation capacity of ASC after tamoxifen treatment [ 42 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to the present results, it was postulated that tamoxifen does not affect cellular proliferation, vascular endothelial growth factor secretion and apoptosis of ASC [ 42 ]. Furthermore, the gene expression assessment demonstrated no impairment in the differentiation capacity of ASC after tamoxifen treatment [ 42 ]. The results of the study at hand are another keystone to depict the controversial facts about ASC and parallel tamoxifen treatment.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…When ex-vivo breast cancer cells were co-cultured with ADSCs-enriched medium and tamoxifen, tamoxifen treatment simultaneously reduced the differentiation of ADSCs into adipogenic and osteogenic cells, while also inhibiting their proliferation in a dose-dependent manner ( 12 ). While these findings contradict the results of a study by Boemi et al , which compared ADSCs from women with breast cancer who were taking tamoxifen to ADSCs from menopausal women, suggesting that tamoxifen (20 mg/day) had no effect on ADSC apoptosis compared to the control group ( 13 ). MDA-MB-231 and ADSCs underwent treatment with paclitaxel (1.0 µM) or low-dose paclitaxel (0.1 µM) in combination with a histone deacetylase inhibitor, providing additional insights into the interaction between ADSCs and chemotherapy.…”
Section: Discussioncontrasting
confidence: 95%
“…Autologous fat grafting is widely utilized for soft tissue filling and reconstructive surgery because of its good biocompatibility and minimal invasiveness. 1 , 2 However, the poor retention rate of fat grafts is a pressing problem that needs to be addressed. 3 Grafted fat tissue must be revascularized as soon as possible in the recipient area to achieve a satisfactory retention rate.…”
mentioning
confidence: 99%